2020
DOI: 10.1021/acs.molpharmaceut.9b01210
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of pH on the Structure and Bioavailability of Imidazobenzodiazepine-3-Carboxylate MIDD0301

Abstract: We describe the effects of pH on the structure and bioavailability of MIDD0301, an oral lead compound for asthma. MIDD0301 interacts with peripheral GABA A receptors to reduce lung inflammation and airway smooth muscle constriction. The structure of MIDD0301 combines basic imidazole and carboxylic acid function in the same diazepine scaffold, resulting in high solubility at neutral pH. Furthermore, we demonstrated that MIDD0301 can interconvert between a sevenmembered ring structure at neutral pH and an acycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In contrast to other chiral imidazodiazepines such as SH‐053‐CH 3 , MIDD0301S has the same IC 50 . We have shown that MIDD0301 adopts two stable conformations and can undergo hydrolysis to form an open keto form at very low pH (Roni et al, 2020). The two stable conformations of chiral imidazodiazepines can be detected by 1 H‐nuclear magnetic resonance.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to other chiral imidazodiazepines such as SH‐053‐CH 3 , MIDD0301S has the same IC 50 . We have shown that MIDD0301 adopts two stable conformations and can undergo hydrolysis to form an open keto form at very low pH (Roni et al, 2020). The two stable conformations of chiral imidazodiazepines can be detected by 1 H‐nuclear magnetic resonance.…”
Section: Resultsmentioning
confidence: 99%
“…Like all chiral imidazodiazepines in this class, PI310 and PI320 have two stable configurations that can be distinguished by nuclear magnetic resonance. 21 Next, we investigated the affinity of these compounds at the GABA A R. Here, rat brain homogenate was used in combination with 3 H-flunitrazepam. GABA A R subtypes that bind flunitrazepam consist of α 1−3,5,6 β 1−3 γ 1−3 /δ GA-BA A Rs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The coupling was achieved with the acid chloride of MIDD0301 in the presence of N -methylmorpholine, resulting in PI310 at a 32% overall yield. Like all chiral imidazodiazepines in this class, PI310 and PI320 have two stable configurations that can be distinguished by nuclear magnetic resonance …”
Section: Results and Discussionmentioning
confidence: 99%
“…To overcome this problem, a 1:4 ratio of water and THF was employed, which remained as a biphasic solution throughout the process. The initial 8 equiv of sodium hydroxide were reduced to 4 equiv and the reaction temperature lowered from 78 to 50 °C, achieving full conversion of the starting material within 4 h. Our group recently reported the pH-dependent equilibrium between a closed seven-membered ring and the open-ring acyclic benzophenone structure of MIDD0301 . Although both compounds are interconvertible without racemization, they exhibited different aqueous solubility.…”
Section: Resultsmentioning
confidence: 99%
“…MIDD0301 is a clinical drug candidate for asthma that binds allosterically to the γ amino butyric acid type A receptor (GABA A R) . Several in vivo studies have shown that inhaled and orally administered MIDD0301 reduced airway smooth muscle constriction and lung inflammation without toxicity. …”
Section: Introductionmentioning
confidence: 99%